The Mexican Experience of the NAPAPI Revision Process - María Esther Coronado Martínez (Contexto Internacional, 2016)
Abstract In 2007, Mexico, the USA and Canada signed the North America Plan for Avian and Pandemic Influenza (NAPAPI). During the 2009 H1N1 pandemic, the plan was implemented for the first time. After the emergency, the three countries decided to review their response, and update the plan. This study analyses the trinational negotiations towards the amended NAPAPI of 2012. More specifically, it focuses on the intergovernmental synergies and intersectoral dynamics in Mexico's domestic policy-making process relevant to the negotiations. The general research questions guiding this analysis were: how do domestic intergovernmental processes and intersectoral dynamics in Mexico affect the crafting of foreign policy? And how does international cooperation affect the domestic public health agenda? The study seeks to answer these questions by examining the H1N1 pandemic, the challenges facing Mexico in the course of the pandemic, and its experience of NAPAPI. It also examines the domestic policy process in Mexico for revising this trinational plan.